PROSPECTS AND PROBLEMS OF DIGITIZATION OF EDUCATION: EXPERIENCE OF THE LEADING COUNTRIES OF THE WORLD - Binytska, Kateryna; Shcherbiak, Iurii; Binytska, Olena; Nahornyi, Yaroslav (Mountain School of Ukrainian Carpaty, 2022)
The purpose of the article is to study the experience of the leading countries of the world regarding the advantages and problems of digitization of education. It is summarized that at the current stage of the development of pedagogical science, scientists do not have a single approach to the term digitalization in education. At the same time, all researchers note that there is still no alternative to the use of digital technologies in education. The article identifies the main directions of digitalization of the educational process: the use of immersive, cloud, mobile and Internet learning technologies, distance education, mass open online courses, gamification of the educational process, development of digital libraries and campuses of educational institutions, etc. In general, the digitalization of education has both expected advantages and problems. Advantages include: digital learning stimulates the organs of sight and hearing. Therefore, the educational material is easier to understand; іnteractive learning increases the quality of education; digital devices have become available to a wide range of people and accordingly digital skills are the skills of the 21st century; there is an increase in work efficiency for teachers and a decrease in workload; implementation of the idea “without paper notebook or book” to preserve the environment and reduce the burden on students during the trip to school;ensuring the provision of educational services in conditions of lockdown, cataclysms or, for example, during military conflicts (as in Ukraine). The problems include:lack of full-fledged ecosystems of digital education. Material and technical problems in training, in particular, free access to the Internet, provision of the necessary gadgets; despite the high quality of distance education in the leading countries of the world, students still lose in the expected progress; due to the lack of formed digital competences, the workload of teachers has increased; not all participants of the educational process like the fact that learning takes place only remotely; in all the diversity of digital education, one cannot forget about the basic carrier of knowledge – “paper and pen”; preservation of the principle of individuality in the educational process. Network environment maintenance. Having analyzed the experience of digitalization in the leading countries of the world, the key changes that can be traced today in education in this direction have been determined.